COMMUNICATION STRATEGY FOR TAX AMNESTY SOCIALIZATION - Dannisa Maulita Lestari; Indra Novianto Adibayu Pamungkas (UNIVERSITAS KEBANGSAAN, 2019)
Abstract: The Tax Amnesty Program in Indonesia has been successfully implemented by the Directorate General of Taxes. With the communication strategy made by the Directorate General of Taxation P2Humas Directorate of Taxes, the tax amnesty program was awarded the world level organized by the International Public Relations Association (IPRA), the Golden World Award for Excellent in Public Relations 2018 in the Public Sector. IPRA considered that this tax amnesty program has bern achieved and remarkable achievements from the time which took place in mid-2016 to 2017. The purpose of this study is to know rhat communication strategie s such as what was done by the P2Humas Directorate in disseminating the Tax Amnesty program. This research use qualitative methods with qualitative descriptive research and constructivist paradigms. Based on the results of this study, it was found that the communication strategy carried out by the P2Humas Directorate in disseminating the Tax Amnesty program was to use all communication media, establish cooperative relations and conduct face-to-face socialization. Keywords: communication strategy, Public Relations, Amnesty Tax